Transient daily heat stress during the early reproductive phase disrupts pod and seed development in Brassica napus L. - Chen, Sheng; Stefanova, Katia; Siddique, Kadambot HM; Cowling, Wallace A (Wiley, 2020)
© 2020 The Authors. Food and Energy Security published by John Wiley & Sons Ltd. and the Association of Applied Biologists.